Operative spinal trauma: Thromboprophylaxis with low molecular weight heparin or a direct oral anticoagulant. (13th April 2019) - Hamidi, Mohammad; Zeeshan, Muhammad; Kulvatunyou, Narong; Mitra, Hari S.; Hanna, Kamil; Tang, Andrew; Northcutt, Ashley; O'Keeffe, Terence; Joseph, Bellal
Abstract: Essentials Operative spine trauma patients are at increased risk of venous thromboembolism (VTE). Direct oral anticoagulants (DOACs) may have a favorable efficacy and safety in spine trauma. Patients on DOACs had lower rates of VTE in comparison to low molecular weight heparin. DOACs did not augment the risk of surgical bleeding (transfusion, decompressive procedures). Background: Spinal trauma patients are at high risk for venous thromboembolism (VTE). Objective: To compare the impacts of direct oral anticoagulants (DOACs) and low molecular weight heparin (LMWH) as thromboprophylactic agents on outcomes in operative spinal trauma patients. Methods: A 2‐year (2015‐2016) retrospective cohort analysis of such patients (spine Abbreviated Injury Scale [AIS] ≥ 3 and other AIS < 3) who received LMWH or DOACs was performed. Propensity score matching (1:2 ratio) followed stratification into two groups. Outcomes included rates of deep vein thrombosis (DVT) and/or pulmonary embolism (PE), packed red blood cell (pRBC) transfusion, operative interventions for spinal cord decompression, and mortality. Results: Of 6036 patients, 810 (270 receiving DOACs; 540 receiving LMWH) were matched. The mean age was 62 ± 15 years, 58% were male, and the median Injury Severity Score was 12 (10‐18). Matched groups were similar in demographics, injury parameters, emergency department vital signs, hospital stay, rates of inferior vena cava filter placement, and timing of initiation of thromboprophylaxis. The overall rate of in‐hospital DVT was 5.6%, the overall rate of in‐hospital PE was 1.6%, and the mortality rate was 2.5%. DOAC patients were less likely to develop DVT (1.8% vs 7.4%) and PE (0.3% vs 2.1%). There were no differences in postprophylaxis pRBC transfusion requirements, postprophylaxis decompressive procedures on the spinal cord, or mortality. Conclusion: In operative spinal trauma patients, thromboprophylaxis with DOACs appears to be associated with lower rates of DVT and PE. Further prospective clinical trials should evaluate the role of DOACs in preventing VTE events in spinal trauma patients.